Análise de medidas mitigatórias de impactos antrópicos negativos à mastofauna em uma paisagem rural em São Carlos-SP - Tezori, Rogerio Franco Flores (2011)
The human pressures on natural environments generate fragmentation and loss of habitat, one of the main threats to biodiversity. Using the terrestrial mammals as indicators, it were evaluated the ecological corridor Embrapa- Fazenda Engenho Velho (Old Mill Farm) and a silvopastoral system to determine if they actually mitigate the negative impacts of local farming. Four linear transects were laid in two fragments of semideciduous forest in the ecological corridor that connects them and made 24 observations, including the branch tunnels (one with 0.9 m in diameter and another with 2.5 x2m) under the highway Guilherme Scatena (that divides the ecological corridor) and its coasting. With the data was constructed a dendrogram of similarity (Jaccard coefficient). In the silvopastoral system and conventional grazing, were placed four cages (15x15x40cm) in each and 20 observations were made. The results demonstrate the presence of 27 species in the fragments, seven of which use the corridor and only two uses the tunnel passage. The similarity between the fragments is high (65%), but decays over the corridor (44%) and the tunnel passage (19%), which shows that the ecological corridor is not fulfilling its role of facilitating the exchange of individuals among the fragments for greater genetic variability in local populations. Furthermore, the coasting had 11 species (45% similarity with fragments), but no individual was found run over, suggesting that in this case, the speed bumps installed on the highway are the most effective tools for conservation than the actual tunnel passage. The largest tunnel presented seven species, but lacks the vegetation in the surroundings unlike smaller tunnel, suggesting that for the branch tunnels, it is extremely important to their size. In the silvopastoral system were found four individuals from three genera (Calomys, Akodon and Oligorizomys) and in the common grazing, eight individuals of the genus Calomys, suggesting that silvopastoral systems are better to maintain species richness. We conclude that there are viable alternatives to improve production and maintain biodiversity, native vegetation with the best connection, but the deployments must be accomplished effectively and not only for law enforcement, without ever having a monitoring of its function, as occurs in most rural areas of the country subjected to this type of activity. Also we can t think that the mere fact of clearing vegetation and deploy these systems are solutions to the environmental crisis, but to optimize the use of land already cleared for such deployment.